Mutual Fund Liquidity Costs. Issue 2 (9th November 2016) - Fulkerson, Jon A.; Riley, Timothy B.
Abstract : One dollar in purchases or redemptions generates an average cost of 0.006 for US equity mutual funds during the period 1997‐2009, approximately 70% lower than prior estimates derived from older data. However, large cross‐sectional differences exist between funds. Many funds have costs near zero, but funds that hold relatively illiquid equities, have relatively concentrated portfolios, and manage relatively large amounts of assets have average liquidity costs significantly greater than the full sample average. Furthermore, despite a large difference in underlying asset liquidity, US bond funds and US equity funds have similar average liquidity costs.